From Adolescents to Early Learners: Adapting Role-Playing for Pancasila Education in Early Childhood Contexts - Risdayanti Risdayanti; Nurhikmah Nurhikmah (Lia Center of Research and Education, 2025)
This study reexamines the role of the Role-Playing method in Pancasila Education, originally implemented with seventh-grade students at SMPN 6 Satap Baraka, to explore its broader implications for early childhood contexts. The initial classroom action research, conducted over two cycles with three sessions each, demonstrated that conventional teacher-centered methods had failed to actively engage learners, resulting in achievement scores below the Minimum Mastery Criteria (KKM). By contrast, the introduction of role-playing produced significant improvements: average learning outcomes increased from 60.41 in Cycle I to 81.87 in Cycle II, while student activity levels rose from 65% to 98%. These findings highlight the effectiveness of role-playing in creating dynamic, participatory, and meaningful learning environments, fostering both engagement and value internalization. While the empirical data were collected at the secondary level, the developmental nature of role-playing—anchored in play, empathy, and perspective-taking—suggests even stronger pedagogical relevance for early childhood education, where play is the primary mode of learning. The study therefore argues that role-playing represents not merely a remedial strategy for adolescents but a foundational approach for cultivating Pancasila values in early learners.